Description of an intensive nutrition therapy in hospitalized adolescents with anorexia nervosa. (April 2016) - Pettersson, Cecilia; Tubic, Bojan; Svedlund, Anna; Magnusson, Per; Ellegård, Lars; Swolin-Eide, Diana; Forslund, Heléne Bertéus
Abstract: Objective: To describe an intensive nutrition therapy for hospitalized adolescents and young adults with anorexia nervosa (AN) in terms of body weight, body composition, energy balance and food related anxiety. Method: Twenty-six young females, 16–24 years of age, with AN were invited to participate at admission to a specialized eating disorder unit in Göteborg, Sweden. Intensive nutrition therapy comprised 12 weeks on a structured meal plan. Six meals were served daily, in combination with high-energy liquid nutritional supplements from start. Energy and nutrient intakes, energy expenditure, body composition and food related anxiety were measured during the study. A 3-month follow-up of body weight and food related anxiety was conducted. Results: Twenty-one patients participated. The total daily energy intake was, during the first week of treatment, (mean ± SD) 3264 ± 196 kcal (74 kcal/kg), and decreased gradually during treatment to 2622 ± 331 kcal (49 kcal/kg). Total daily energy expenditure was initially 1568 ± 149 kcal and increased gradually to 2034 ± 194 kcal. Patients gained on average 9.8 ± 2.1 kg and body mass index increased from 15.5 ± 0.9 to 19.0 ± 0.9 kg/m 2 . Body fat increased from 13 ± 6% to 26 ± 6%. Fat free mass remained unchanged, but skeletal muscle mass increased from 16.7 ± 2.0 to 17.6 ± 2.4 kg, p = 0.009. Patients' food related anxiety decreased significantly during treatment and was still unchanged 3 months later. Conclusion: The presented intensive nutrition therapy with initially high energy and nutrient intakes produced substantial weight gain, increased fat and muscle mass and decreased food related anxiety in AN patients, without any clinical side effects. Highlights: This treatment model combines rapid refeeding with medical nutrition therapy. High energy and nutrient intakes are effective in anorexia nervosa inpatient treatment. Food related anxiety in anorexia nervosa decreases with intensive nutrition therapy.